The Factors Influencing Intention to Use IM3’s Instagram: An Empirical Study - Wirawan, Made; Sugiat, Maria Apsari (Manunggal Halim Jaya, 2026)
The rapid growth of internet users in Indonesia is driven by the advancement of mobile phone technology, cellular operators, and social media platforms. Millennials and Generation Z dominate Indonesia's mobile internet users, primarily using it to access social media. One of the most popular platforms among these generations is Instagram. It’s often used for entertainment, information, trends, and promotions. IM3, a mobile operator targeting Millennials and Generation Z, utilizes Instagram (@IndosatIM3) for product promotion and consumer engagement through engaging and informative content. This study examines how Perceived Ease of Use, Perceived Usefulness, Monetary Benefit, and Information Reliability affect users’ Intention to Use Instagram @IndosatIM3. Data were collected from 341 purposively selected respondents via online questionnaires. Using SmartPLS for data analysis, the study found that Perceived Ease of Use have the strongest positive effects on Intention to Use, while Perceived Usefulness and Information Reliability show no significant effect on Intention to Use. These findings offer practical insights for improving social media marketing strategies aimed at Millennials and Generation Z.